Reestablishment of Baccharis heeringiana (Compositae: Astereae) and a new record for Uruguay - Valtierra, María Victoria; Heiden, Gustavo; Bonifacino, José M. (Phytotaxa, 2023)
During the taxonomic revision of ‘carquejas’ (Baccharis sect. Aphyllae and B. sect. Caulopterae) from Uruguay, and following a comprehensive study of the protologues, type materials, and recently collected specimens, we conclude that B. sagittalis and B. heeringiana are distinct species. Therefore, we propose the recognition of B. heeringiana as an independent taxonomic entity. Baccharis heeringiana has wider wings than B. sagittalis (6.5–20 mm vs. 2–6 mm wide), longer corollas in staminate florets (5.5–8 mm vs. 3.5–4.5 mm long), longer styles in pistillate florets (4–6.5 mm vs. 2–2.6 mm long) and distinct pappus elements (barbellate vs. scabrid bristles). It grows in waterlogged sites with hydromorphic soils in Eastern South America from Bahia, in Northeast Brazil, and south to the Eastern Uruguayan departments of Cerro Largo and Rocha. A distribution map, field photos, and an illustration are also provided.